1999
DOI: 10.1074/jbc.274.21.14963
|View full text |Cite
|
Sign up to set email alerts
|

Two Amino Acids within the α4 Helix of Gαi1Mediate Coupling with 5-Hydroxytryptamine1BReceptors

Abstract: We previously reported that residues 299 -318 in G␣ i1 participate in the selective interaction between G␣ i1 and the 5-hydroxytryptamine 1B (5-HT 1B ) receptor (Bae, H., Anderson, K., Flood, L. A., Skiba, N. P., Hamm, H. E., and Graber, S. G. (1997) J. Biol. Chem. 272, 32071-32077). The present study more precisely defines which residues within this domain are critical for 5-HT 1B receptormediated G protein activation. A series of G␣ i1 /G␣ t chimeras and point mutations were reconstituted with G␤␥ and Sf9 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 49 publications
5
37
0
1
Order By: Relevance
“…Furthermore, these results support a role for charge-charge complementation in receptor/G␣ coupling ( Fig. 3 A and B) as postulated for other GPCRs, including rhodopsin and the 5-HT 1A serotonin receptor (20).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Furthermore, these results support a role for charge-charge complementation in receptor/G␣ coupling ( Fig. 3 A and B) as postulated for other GPCRs, including rhodopsin and the 5-HT 1A serotonin receptor (20).…”
Section: Resultssupporting
confidence: 60%
“…D2N engages a triad of residues on the ␣4 helix and ␤6 strand (Q304/E308 and T321, respectively; Fig. 2B) that were implicated in studies using G␣ chimera (19)(20)(21) in the coupling specificity and GEF activity of the 5-HT 1A serotonin receptor. Binding of D2N results in displacement of the G␣ i1 ␤6 strand with respect to the unbound state ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conservation of the Cterminal residues within one family requires participation of additional regions of G␣ to achieve fine receptor tuning. For example, Gln 304 and Glu 308 in the ␣ 4 helix of G i ␣ 1 are important to the selectivity of the 5-hydroxytryptamine receptor for G i ␣ 1 over G t ␣ (20). Chimeric G t ␣/G i ␣ proteins have been very instrumental in gaining insight into the G i ␣ 1 /5-hydroxytryptamine receptor selectivity (20), but would not be helpful in elucidating the C-terminal determinants of the G t ␣/R* interaction since the C termini of G t ␣ and G i ␣ are almost identical, and R* potently stimulates G i ␣ in vitro (13).…”
Section: Discussionmentioning
confidence: 99%
“…The ␣4-helix-␣4/␤6-loop domain, first described as an effector domain, has been shown to be important for 5-HT 1B receptor coupling to G i1 (11). Later it was demonstrated that Gln-304 and Glu-308 in the ␣4-helix of G i1 ␣ are important for 5-HT 1B receptor coupling (18). However the generality of the role for the ␣4-helix-␣4/␤6-loop domain in receptor coupling selectivity has not been determined.…”
mentioning
confidence: 99%
“…The digested PCR fragment was inserted into the BglII and HindIII sites of the Chi13 plasmid (11). Functional characterization of all bacterial subunits included GTP␥S binding, AlF 4 Ϫ -dependent conformational change (measured as an increase in intrinsic tryptophan fluorescence) or binding to the cGMP phosphodiesterase ␥-subunit (11,18,19).…”
mentioning
confidence: 99%